Lacomucinaea, a new monotypic genus in Thesiaceae (Santalales) - Nickrent, Daniel Lee; García, Miguel Angel (Phytotaxa, 2015)
A new monotypic genus from southern Africa is described based on Thesium lineatum. Lacomucinaea lineata has a number of vegetative and floral morphological features that differ from Thesium and other members of Thesiaceae. An apparently unique feature of the plant is the presence of succulent, fusiform, terete leaves that are caducous, eventually leaving a persistent petiolar stub. The stem surface shows striations formed by cortical fibers inside raised ridges. Anatomically, this type of primary phloem fiber bundle also occurs in Osyridicarpos. A molecular phylogenetic analysis using nuclear ribosomal ITS and the chloroplast trnLF spacer for representatives of all genera in Thesiaceae showed that Lacomucinaea is sister to Osyridicarpos, further supporting this relationship suggested by stem anatomy characters. Recognizing this taxon as a distinct genus results in the genus Thesium being monophyletic. A key to all genera in Thesiaceae is provided.